Identifikasi Korelasi Minat Terhadap Kemampuan Analisis Siswa pada Konsep Usaha dan Energi - Zakiyyatul Miskiyyah; Winny Liliawati; Dadi Rusdiana (Faculty of Science and Education, UIN Walisongo Semarang, 2021)
The research was conducted to identify the correlation between interest in learning towards students' analytical skills on the concept of work and energy. The research method used is descriptive quantitative with purposive sampling technique of determining the sample. The research sample consisted of 28 people with the characteristics of 20 girls and 8 boys in Senior High School Bandung. The instruments used were questionnaires and tests. The results showed that students' interest in the concept of work and energy was at a very high criterion of 21.43% and a high criterion of 78.57%. The students' analytical skills were in the low criteria of 37% and very low of 63%. Based on calculations using the SPSS IBM 23, the Cramer V value was 0,000 (less than 0.05) so it can be concluded that there is a correlation between student interest in learning and analytical skills on the concept of work and energy. The results of this study indicate the importance of student interest in learning as a provision for receiving learning, especially in students' analytical skills. Therefore, teachers are expected to create a pleasant learning atmosphere to increase student interest in learning and analytical skills.